Re-purchasing tourists’ development guidelines under the context of VUCA world for the persistence of the wellness tourism business in Prachinburi province - Julatha, Watcharaporn; Phumdej, Supisa; Intasuwan, Patthamon (Journal of Industrial Business Administration, 2024)
This research aims to study 1) types of re-purchasing tourists of the wellness tourism business in Prachinburi Province 2) behaviours of re-purchasing tourists for each type in the wellness tourism business in Prachinburi Province and 3) marketing strategies that are appropriate for re-purchasing tourists’ behaviours.To lead to suggesting guidelines for re-purchasing tourists’ development guidelines under the context of VUCA world for the persistence of the wellness tourism business in Prachinburi Province. By collecting data from 2 main groups: 1) tourists who use tourism goods and services in Prachinburi Province During the time the research was conducted, 400 people received questionnaires. Use analytical methods using mathematical packages, and interpret the results with statistical values, including frequency, percentage, mean, and standard deviation, and 2) 30 specific wellness tourism business entrepreneurs in Prachinburi Province using semi-structured interviews. Using content analysis methods and interpret the results in a descriptive manner. The research found that health tourists who come back to buy again are family tourists. The number 1 business group in which tourists have repeated trips or used services is the health food restaurant business group 36 %, with the number of repeat trips or health promotion services in Prachinburi province as high as 12 times/year. And marketing strategies used by tourist attractions and wellness tourism service providers through creating tourism experiences with all five senses that are most appropriate to repeat tourist behaviours are: 1) taste sense 2) sight sense and 3) touch sense. In this regard, the other two marketing strategies are at the high and medium levels: smell sense was at a high level and sound sense was at a moderate level, respectively